ВОЗМОЖНОСТИ МЕТОДА ОБЪЕМНОЙ КОМПРЕССИОННОЙ ОСЦИЛЛОМЕТРИИ В ПРОГНОЗИРОВАНИИ КАРДИОВАСКУЛЯРНОГО РИСКА У БОЛЬНЫХ АРТЕРИАЛЬНОЙ ГИПЕРТОНИЕЙ В ОБЩЕЙ ВРАЧЕБНОЙ ПРАКТИКЕ - Н. В. Страхова; А. А. Зуйкова (SINAPS LLC, 2013)
It is considered the possibility of use of an assessment of a condition of haemodynamics by volume compression oscillometry in definition of cardiovascular risk. The scale of prediction of risk in patients with arterial hypertension by the data of volume compression oscillometry and risk factors is developed.